Nikochares - Xenophon : Einleitung, Übersetzung, Kommentar - Orth, Christian (Fragmenta comica, 2015)
Nikochares -- Philonikos -- Philyllios -- Poliochos -- Polyzelos -- Sannyrion -- Theochares -- Xenophon